Development of an isothermal CO2 absorption process using DMC and PEG400 for carbon capture and storage technology - Ferdiansyah Iqbil Qouli; Iqlima Huda Sahiba; Yuli Rahmawati Dwi Rahayu Ningrum; Rizky Tetrisyanda; Gede Wibawa; Wahyudiono Wahyudiono; Rendra Panca Anugraha (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study aims to develop and evaluate a green binary solvent system based on dimethyl carbonate (DMC) and polyethylene glycol 400 (PEG400) for physical CO2 absorption. Efficient and environmentally benign solvents are essential to support large-scale decarbonization efforts. The DMC–PEG400 system was formulated at molar ratios of 1:2, 1:3, and 1:4 to assess its absorption performance. Isothermal solubility experiments were performed at 303.15–323.15 K and 3–7 bar, complemented by Fourier Transform Infrared (FTIR) spectroscopy to elucidate the absorption mechanism. The FTIR spectra showed the emergence of characteristic CO2 vibrational bands without alterations to the solvent’s fingerprint region, confirming that CO₂ uptake proceeds through physical dissolution rather than chemical interaction. The DMC–PEG400 mixtures demonstrated clear temperature and pressure dependencies typical of physical solvents, with solubility decreasing at elevated temperatures and increasing proportionally with pressure. Among the tested formulations, the 1:3 molar ratio exhibited the highest absorption capacity, achieving 0.0606 mole CO₂/mole solution at 303.15 K and 7 bar. This performance arises from an optimal balance between interaction sites provided by PEG400 and the moderate viscosity needed to facilitate efficient CO2 diffusion. In contrast, the 1:4 mixture displayed reduced capacity due to excessive viscosity and limited free volume. Overall, the results highlight the promising potential of DMC–PEG400 mixtures, particularly at the 1:3 ratio, as tunable and sustainable physical solvents for CO₂ capture. Their favorable solubility behavior, stability, and benign chemical nature position them as viable candidates for next-generation carbon capture and storage (CCS) technologies.